COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN SAMPAH DI PANTAI TELUK PENYU KABUPATEN CILACAP - Oktavia Ulya, Tri; Rina Herawati, Augustin; Subowo, Ari (Journal of Public Policy and Management Review, 2024)
This research focuses on the collaboration process in waste management at Teluk Penyu Beach. Waste problems often occur in one of the tourist icons in Cilacap Regency, so collaboration from multiple stakeholders is needed to manage the problem. The purpose of this research is to describe and analyse collaborative governance in waste management at Teluk Penyu Beach, as well as identify and analyse the factors that influence collaborative governance in waste management at Teluk Penyu Beach. The type of research used is descriptive research with a qualitative approach. The data collection techniques used were interviews, observation, and documentation. The theory used in this research is Ansell and Gash's theory which consists of starting conditions, institutional design, facilitative leadership, and collaboration process (face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes). The results of this study show that (1) collaborative governance in waste management at Teluk Penyu Beach has implemented the five dimensions of the collaboration process quite well. (2) Factors that influence the collaboration process in waste management at Teluk Penyu Beach include starting conditions, institutional design, and facilitative leadership, but the institutional design dimension is still not optimal because there is no legal basis that specifically regulates the collaboration process in waste management at Teluk Penyu Beach, Cilacap Regency.